The [M(NHC)] (M=Pd, Pt) fragment in the synthesis of heteronuclear clusters - Liu, Yu (2014)
While heteronuclear clusters having phosphine ligands are well-known, those containing nitrogen heterocyclic carbenes (NHCs) seem less explored. This describes work on the synthesis and characterization of new heteronuclear clusters of the heavier groups 8 (Ru and Os) and 10 (Pd and Pt) metals containing nitrogen heterocyclic carbenes (NHC).